2016
DOI: 10.5194/hess-20-1903-2016
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental irrigation potential and impact on downstream flow of Karkheh River basin in Iran

Abstract: Abstract. Supplemental irrigation of rainfed winter crops improves and stabilises crop yield and water productivity. Although yield increases by supplemental irrigation are well established at the field level, its potential extent and impact on water resources at the basin level are less researched. This work presents a Geographic Information Systems (GIS)-based methodology for identifying areas that are potentially suitable for supplemental irrigation and a computer routine for allocating streamflow for suppl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Roughly this potential amounts to in (2008a) for Syria, suggesting that allocating the same amount of water used for fully irrigated summer cotton crop to a partially irrigated winter wheat crop would result in more than doubling the area under irrigation. The present study confirms the findings of Hessari et al (2016), who used lumped modelling to find suitable SI areas in the whole of the upper KRB and to predict the expected consequences of water flowing downstream to Karkheh dam. The authors reported that under normal flow conditions, about 2060 km 2 , which represents 13% of the rainfed crop areas and 28% of suitable areas, could be provided with SI in autumn and spring.…”
Section: Spatial and Cell-based Water Allocationsupporting
confidence: 89%
See 2 more Smart Citations
“…Roughly this potential amounts to in (2008a) for Syria, suggesting that allocating the same amount of water used for fully irrigated summer cotton crop to a partially irrigated winter wheat crop would result in more than doubling the area under irrigation. The present study confirms the findings of Hessari et al (2016), who used lumped modelling to find suitable SI areas in the whole of the upper KRB and to predict the expected consequences of water flowing downstream to Karkheh dam. The authors reported that under normal flow conditions, about 2060 km 2 , which represents 13% of the rainfed crop areas and 28% of suitable areas, could be provided with SI in autumn and spring.…”
Section: Spatial and Cell-based Water Allocationsupporting
confidence: 89%
“…The present study confirms the findings of Hessari et al . (2016), who used lumped modelling to find suitable SI areas in the whole of the upper KRB and to predict the expected consequences of water flowing downstream to Karkheh dam. The authors reported that under normal flow conditions, about 2060 km 2 , which represents 13% of the rainfed crop areas and 28% of suitable areas, could be provided with SI in autumn and spring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its discharge flows into the transboundary Hawizeh marshes that straddle the Iraqi and Iranian border (Masih et al 2011, Hessari et al 2012). The total annual renewable water resource (both surface and groundwater) is estimated at 8.6 × 10 9 m 3 /yr of which 2.5 × 10 9 m 3 /yr was the total consumptive use in 1993-1994.…”
Section: The Karkheh Rivermentioning
confidence: 99%
“…Improvement of water productivity is an upside preference in agricultural strategies of Iran (Asmala, 2012). To increase in amount of water productivity and crop in the upper plains of the basin supplemental irrigation has been recommended (Hessari et al, 2012).…”
Section: Study Areamentioning
confidence: 99%